2010
DOI: 10.1111/j.1365-3156.2009.02463.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitrosensitivity ofPlasmodium falciparumto conventional and novel antimalarial drugs in Papua New Guinea

Abstract: Summaryobjective Recent clinical studies have shown high rates of malaria treatment failure in endemic areas of Papua New Guinea (PNG), necessitating a change of treatment from chloroquine (CQ) or amodiaquine (AQ) plus sulphadoxine-pyrimethamine to the artemisinin combination therapy (ACT) artemether plus lumefantrine (LM). To facilitate the monitoring of antimalarial drug resistance in this setting, we assessed the in vitro sensitivity of Plasmodium falciparum isolates from Madang Province.methods A validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 50 publications
(70 reference statements)
6
23
4
Order By: Relevance
“…Alternatively, they can represent acquired resistance on the background of previous antimalarial resistance phenotypes. Previous studies of P. falciparum have documented positive correlations between the IC 50 s for the quinoline class of compounds and related drugs (38,40). The correlation of NQ with AQ, PIP, MFQ, and AS observed in P. falciparum isolates in the present study was similar to that reported from neighboring Papua New Guinea (38).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Alternatively, they can represent acquired resistance on the background of previous antimalarial resistance phenotypes. Previous studies of P. falciparum have documented positive correlations between the IC 50 s for the quinoline class of compounds and related drugs (38,40). The correlation of NQ with AQ, PIP, MFQ, and AS observed in P. falciparum isolates in the present study was similar to that reported from neighboring Papua New Guinea (38).…”
Section: Discussionsupporting
confidence: 80%
“…The IC 50 s of NQ in P. falciparum isolates (median IC 50 , 8.0 nM; interquartile range, 26.5 nM) were similar to those reported in culture-adapted P. falciparum isolates from Papua New Guinea (geometric mean, 7.0; 95% confidence interval [CI], 5.5 to 8.8 nM) (38). Our ex vivo study presents additional evidence for NQ's potent activities against highly CQ-resistant isolates of P. falciparum and P. vivax, revealing lower IC 50 s for NQ than for all of the standard drugs with the exception of AS.…”
Section: Discussionsupporting
confidence: 54%
“…This result reveals a pleiotropic role for this recently emerged pfcrt allele in modulating parasite susceptibility to clinically important antimalarials. This role differs from what is generally observed in Africa with the PfCRT CVIET haplotype or even the PfCRT SVMNT haplotype in Papua New Guinea (29,30). This effect of C350R on QN and MQ, however, was not replicated in field isolates, underscoring a complex genetic basis of susceptibility in the field.…”
Section: Discussioncontrasting
confidence: 46%
“…It is suspected that cross-resistance might occur between PPQ and other quinoline drugs because of structural similarities of these drugs and possibly shared modes of ac- tion (46). Studies showing correlation between in vitro susceptibilities of parasite isolates to CQ and PPQ (20,22,24,25,32) and demonstration of elevated resistance to PPQ in well-characterized laboratory CQ-resistant parasite lines (25,26) suggest a role of the major CQ-resistant marker pfcrt in PPQ resistance. However, it is noteworthy that the difference between the PPQ responses in CQsensitive and -resistant strains which led to the suggestion of cross-resistance between CQ and PPQ resistance was insignificant and only at 3-to 4-fold (Table 2).…”
Section: Discussionmentioning
confidence: 99%